ENHANCING THE POTENCIES OF CHIMERIC ANTIGEN RECEPTOR T CELL (CAR T CELL) BY CRISPR/CAS9 SYSTEM TO ERADICATE RETINOBLASTOMA - Muhammad Yuda Nugraha; Astuti Setyawardani; Yehuda Tri Nugroho Supranoto (OISAA, 2020)
Retinoblastoma (RB) is the most common primary intraocular malignancy of childhood. There is no therapies that can eradicate specifically the whole cancer cells without any side effects. The disialoganglioside 2 (GD2), one of the cancer’s cell markers that can be treated using immunotherapy, is expressed in RB. Through this fact, immunotherapy based on chimeric antigen receptor (CAR)-engineered T cells targeting cancer-specific antigens has shown great potential in treating this cancer. Although in recent studies show that immune cells are not able to destroy cancer cells because in every cancer cells there is protein programmed death ligand 1 (PD-L1). This literature review also shows the potential technology using Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)-CRISPR associated protein (Cas9) method to silence PD-1 in CAR T cell, so PD-L1 can not deactivate CAR T Cell through PD-1 signaling. The combination using CAR T cell and CRISPR-Cas9 will be the great therapy to eradicate RB without any side effect.